Answer:
2Na₃PO₄ + 3CaCl₂ → 6NaCl + Ca₃(PO₄)₂
Step-by-step explanation:
Chemical equation:
Na₃PO₄ + CaCl₂ → NaCl + Ca₃(PO₄)₂
Balance chemical equation:
2Na₃PO₄ + 3CaCl₂ → 6NaCl + Ca₃(PO₄)₂
First step:
Na₃PO₄ + CaCl₂ → NaCl + Ca₃(PO₄)₂
Left hand side Right hand side
Na = 3 Na =1
P = 1 P = 2
O = 4 O = 8
Ca = 1 Ca = 3
Cl =2 Cl = 1
2nd step:
2Na₃PO₄ + CaCl₂ → NaCl + Ca₃(PO₄)₂
Left hand side Right hand side
Na = 6 Na =1
P = 2 P = 2
O = 8 O = 8
Ca = 1 Ca = 3
Cl =2 Cl = 1
3rd step:
2Na₃PO₄ + 3CaCl₂ → NaCl + Ca₃(PO₄)₂
Left hand side Right hand side
Na = 6 Na =1
P = 2 P = 2
O = 8 O = 8
Ca = 3 Ca = 3
Cl = 6 Cl = 1
3rd step:
2Na₃PO₄ + 3CaCl₂ → 6NaCl + Ca₃(PO₄)₂
Left hand side Right hand side
Na = 6 Na =6
P = 2 P = 2
O = 8 O = 8
Ca = 3 Ca = 3
Cl = 6 Cl = 6